Perspektif Mazhab Hanbali Mengenai Bagi Hasil Tenaga Kerja Dalam Bidang Pertanian di Kecamatan Pallangga Kabupaten Gowa - Hudayanti, Sri; Sabir, Muhammad; Arafah, M. (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
The main problem in this study is that there is a dispute between the land owner and the cultivator so that conflicts often occur because the agreement from the beginning was not appropriate at the time of the harvest agreement, and how is the perspective of the Hanbali School regarding profit sharing in agricultural cooperation in Bontoramba village, Pallangga District, Gowa Regency. The main problems that will be described from the sub-problems are: (1) what is the form of agricultural cooperation carried out by Bontoramba Village, Pallangga District, Gowa Regency? (2) how is the agricultural product sharing system between land owners and cultivators in Bontoramba Village, Pallangga District, Gowa Regency? (3) how is the application of profit sharing in agricultural cooperation according to the Hanbali school in Bontoramba Village, Pallangga District, Gowa Regency? The type of research used is qualitative research or method (field research), namely research that provides a qualitative picture which focuses on field research methods and connects with the Hanbali school. This research is sourced from secondary data and primary data by mananging primary data sourced from interviews with local communities in Bontoramba Village, Pallangga District, Gowa Regency. From the research conducted, the results show that: (1) the from agricultural cooperation carried out in Bontoramba Village is in the from of entering into an agreement with each other in writing or verbally with the presenee of witnesses who witnessed the agreement. (2) the agricultural product sharing system between cand voters and cultivators in accordance with the agreed rules, if the land owner finances all the planting to harvesting processes, the distribution of the results is shared by the land owner, but if the cultivator finances everything and the land owner only receives it. The it is the cultivator who divides the distribution of the harvest. (3) the application of profit sharing in agricultural cooperation, there are rules that are carried out because thare are often disputes with each other at the time of sharing the results due to the lack of trust in each other, then it is applied with a written agreement with the presence of witnesses and involves in the profit sharing of the farmer so as not to there is another disputeAdapun jenis penelitian yang digunakan adalah penelitian kualitatif atau metode (fiel receacrh) yaitu penelitian yang memberikan gambaran secara kualitatif dimana memfokuskan pada metode penelitian lapangan serta menghubungkan dengan mazhab hanbali. Penelitian ini bersumber dari data sekunder dan data primer dengan mengelola data primer yang bersumber dari wawancara masyarakat setempat di Desa Bontoramba Kecamatan Pallangga Kabupaten Gowa.Dari penelitian yang dilakukan, hasil menunjukkan bahwa: (1) Bentuk kerjasama pertanian yang dijalankan di Desa bontoramba dalam bentuk mengadakan suatu perjanjian satu sama lain dengan tertulis atau secara lisan dengan adanya saksi yang menyaksikan suatu perjanjian tersebut. (2) sistem bagi hasil pertanian antara pemilih lahan dan penggarap sesuai dengan aturan yang telah di sepakati jika pemilik lahan yang membiayai semua proses tanam sampai panen maka pembagian hasilnya di bagi oleh pemilik lahan, tetapi jika penggarap yang membiayai semuanya dan pemilik lahan hanya terima jadi maka sih penggarap lah yang membagi pembagian hasil penen. (3) Penerapan bagi hasil dalam kerjasama pertanian adanya aturan yang dilakukan karena sering terjadi perselisihan satu sama lain di saat pembagian hasil dikarenakan tidak adanya kepercayaan satu sama lain, maka di terapkannya dengan perjanjian tertulis dengan adanya saksi dan melibatkan dalam bagi hasil partanian tersebut supaya tidak adanya lagi perselisihan yang terjadi